Ulnar nerve injury after radial extracorporeal shock wave therapy identified with high–resolution ultrasonography: Case Report. - Terán, Paul German (2020)
A 49-year old woman was evaluated for developing bilateral acute medial elbow pain, numbness, and tingling sensation in the fourth and fifth fingers after receiving radial extracorporeal shock wave therapy (rESWT) for bilateral medial epicondylitis. Neurologic examination revealed the presence of Tinel’s sign, paresthesia and impaired two-point discrimination testing over the ulnar side of the fourth and fifth fingers bilaterally. High-resolution ultrasonography demonstrated findings of nerve injury, such as hypoechogenicity and increased diameter of both ulnar nerves.  After conservative treatment, the patient improved her condition demonstrating an apparently acute compressive nerve injury as a result of the therapy. ESWT is used as a promising alternative for the treatment of various musculoskeletal disorders; however, there is limited evidence regarding its side effects, in particular peripheral mononeuropathy. To the authors’ knowledge, this is the first report demonstrating structural damage of a nerve after rESWT with the use of high-resolution ultrasonography.